2016
DOI: 10.1097/icl.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Keratoplasty at 3 Academic Centers from 2002 to 2012

Abstract: Graft failure accounted for approximately 30% to 40% of indications for keratoplasties at three academic centers from 2002 to 2012, which was more than double and in some cases triple that of the EBAA data during this period. These higher frequencies of regrafting may represent a referral bias of patients with complicated cases to academic centers who then require multiple keratoplasties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…A failed graft remains a leading indication for PKP in this study and in other studies. [12][13][14]16,28,29 With increasing endothelial keratoplasties, it remains to be seen whether DSAEK and DMEK failures will continue to rise in Canada, as has been observed in New Zealand. 11 Repeat grafts was a leading indication for PKPs in North America.…”
Section: Discussionmentioning
confidence: 99%
“…A failed graft remains a leading indication for PKP in this study and in other studies. [12][13][14]16,28,29 With increasing endothelial keratoplasties, it remains to be seen whether DSAEK and DMEK failures will continue to rise in Canada, as has been observed in New Zealand. 11 Repeat grafts was a leading indication for PKPs in North America.…”
Section: Discussionmentioning
confidence: 99%
“…Academic centers had more severe and complicated cases in comparison with other services. 69 Another limitation includes the lack of information regarding the exact pathologies grouped as others or nondescribed. In addition, we were unable to evaluate the number of combined CT surgeries with cataract, glaucoma, or retina procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A 10-year study from 2004 at Queen Victoria Hospital in the UK found graft failure to be the leading indication for penetrating keratoplasty 10. Another study, examining statistics from 2002 to 2012, found graft failure to be the most prevalent indication for penetrating keratoplasty at the University of Washington and University of California, Davis in the USA 11. A recent 25-year study, by the University of Auckland, New Zealand, found graft failure to be the second most common indication for any type of corneal transplant 12.…”
Section: Introductionmentioning
confidence: 99%